Perspectives of tree-rings growth for the potential estimation of carbon in Mexico - Reyes-Basilio, Iliana Bibiana; Acosta-Hernández, Andrea Cecilia; González-Cásares, Marcos; Pompa-García, Marín (Instituto de Ecología, A.C., 2020)
Tree growth rings have been useful as a proxy for estimating carbon sequestration in forest ecosystems. Mexico is considered a megadiverse country with a great potential for tree-ring sciences, given its high environmental variability. This study aimed to present a perspective that tree-rings offer in terms of estimating potential carbon uptake in Mexico. We reviewed papers published worldwide, considering studies that comprise dendroecological proxies for the content of stored carbon. The review included 74 studies that were published from 2004 to 2019. Dendroecological investigations of carbon content were conducted mainly since 2012 in Mexico. Most of these studies examined trees species such as Pinus sylvestris and Fagus sylvatica. Adopting a dendroecological approach, associated with allometric techniques, this study offers a great opportunity to promote the development of studies on carbon storage dynamics in Mexico.